Monopolistic Competition and Externalities in The Drug Crypto Market - Raffo, Leonardo; Gómez-Calderón, Diego; Ramírez-Andrade, Carolina (Sociedad y Economía, 2021)
The research purpose is to explain the functioning and dynamics of the crypto drug market. To that end, a model of monopolistic competition with network externalities was developed based on the works Belleflamme & Peitz (2010) and Dixit & Stiglitz (1977). The model’s main prediction is that interdiction policies in these markets tend to be counteracted by the entry of new sellers and the resulting opening of new websites in the dark web. A further finding is that, due to the presence of network externality effects in online drug use, the tightening of interdiction policies produces a feedback effect that leads to a greater number of effective consumers deciding to acquire the devices to access drug platforms on the dark web and, thus, to purchase illegal drugs.